REVISED MIDDLE EOCENE-UPPER OLIGOCENE CALCAREOUS NANNOFOSSIL BIOZONATION FOR THE SOUTHERN OCEAN - C. FIORONI; VILLA, Giuliana; PERSICO, Davide; S. W. WISE; L. PEA (Revue de Micropaléontologie, 2012)
Abstract Calcareous Nannofossils are widely utilized in biostratigraphic studies of Cenozoic sediments. In recent years large datasets have been acquired, and several bioevents showed to be unreliable if correlated over distant areas. New biostratigraphic investigations on middle Eocene-upper Oligocene deep-sea cores have highlighted several omissions in the currently used calcareous nannofossil zonal schemes for the Southern Ocean for this time interval. Quantitative analysis on sediments from seven sites from this area, characterized by abundant, diverse, and moderately to well-preserved nannofloral assemblages, have enabled a revision of the existing zonation for the Southern Ocean, and the development of a high-resolution zonal scheme for the middle Eocene-upper Oligocene. Eleven zones and six subzones are introduced or emended to replace the ten zones and two subzones of the Wei and Wise (1990a) and Wei and Thierstein (1991) zonations, with the identification of several new biohorizons. This has improved regional correlations and the reliability of the identified events for supraregional correlations. Comparisons are made between the proposed zonation and the existing schemes, both on nannofossils from different geographic areas, and on foraminifers from southern high latitude.